PROBLEMS OF BECOMING AND DEVELOPMENT OF BIOETHICS CONSCIOUSNESS FOR THE STUDENTS OF MEDICAL UNIVERSITY - Semydotska, ZH.D.; Cherniacova, I.A. (Ukrainian Journal of Nephrology and Dialysis, 2015)
In the article discussed sources and ways of forming of bioethics consciousness in modern society, basic strategies and complications of becoming of bioethics consciousness for the students of medical university.